2004
DOI: 10.1523/jneurosci.2162-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

HCN2 and HCN1 Channels Govern the Regularity of Autonomous Pacemaking and Synaptic Resetting in Globus Pallidus Neurons

Abstract: The globus pallidus (GP) is a critical component of the basal ganglia circuitry controlling motor behavior. Dysregulation of GP activity has been implicated in a number of psychomotor disorders, including Parkinson's disease (PD), in which a cardinal feature of the pathophysiology is an alteration in the pattern and synchrony of discharge in GP neurons. Yet the determinants of this activity in GP neurons are poorly understood. To help fill this gap, electrophysiological, molecular, and computational approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
195
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(219 citation statements)
references
References 100 publications
(173 reference statements)
24
195
0
Order By: Relevance
“…To assess their involvement in the firing of STN neurons, we used perforated patch-clamp recordings of STN neurons in the presence of synaptic transmission blockers (50 M APV, 20 M CNQX, 20 M GABAzine, and 1-2 M CGP55845) and during perfusion of 2 mM external Cs ϩ to block HCN channels. In contrast to GP neurons (Chan et al, 2004) and in agreement with previous findings (Bevan and Wilson, 1999;Beurrier et al, 2000;Do and Bean, 2003), blockade of HCN channels with Cs ϩ did not affect the firing rate of STN neurons [WSR test;control,6.3 Ϯ 2.8 Hz; Cs ϩ , 6.3 Ϯ 3.3 Hz; n ϭ 6; p ϭ 0.84 ( In STN and GP neurons, stimulation of GABAergic IPSPs transiently hyperpolarizes the membrane potential and produces a pause in firing and a partial or complete reset of the phase of the autonomous oscillation (Bevan et al, 2002a;Chan et al, 2004). In GP neurons, blockade of HCN channels disrupted phase resetting.…”
Section: Hcn and Ca V 3 Channels Are Not Required For Autonomous Actimentioning
confidence: 92%
See 2 more Smart Citations
“…To assess their involvement in the firing of STN neurons, we used perforated patch-clamp recordings of STN neurons in the presence of synaptic transmission blockers (50 M APV, 20 M CNQX, 20 M GABAzine, and 1-2 M CGP55845) and during perfusion of 2 mM external Cs ϩ to block HCN channels. In contrast to GP neurons (Chan et al, 2004) and in agreement with previous findings (Bevan and Wilson, 1999;Beurrier et al, 2000;Do and Bean, 2003), blockade of HCN channels with Cs ϩ did not affect the firing rate of STN neurons [WSR test;control,6.3 Ϯ 2.8 Hz; Cs ϩ , 6.3 Ϯ 3.3 Hz; n ϭ 6; p ϭ 0.84 ( In STN and GP neurons, stimulation of GABAergic IPSPs transiently hyperpolarizes the membrane potential and produces a pause in firing and a partial or complete reset of the phase of the autonomous oscillation (Bevan et al, 2002a;Chan et al, 2004). In GP neurons, blockade of HCN channels disrupted phase resetting.…”
Section: Hcn and Ca V 3 Channels Are Not Required For Autonomous Actimentioning
confidence: 92%
“…In sensory thalamic neurons and GP neurons, HCN channels are important contributors to pacemaking activity (McCormick and Bal, 1997;Robinson and Siegelbaum, 2003;Chan et al, 2004) and to the resetting of rhythmic firing by GABAergic synaptic inputs (McCormick and Bal, 1997;Chan et al, 2004). To assess their involvement in the firing of STN neurons, we used perforated patch-clamp recordings of STN neurons in the presence of synaptic transmission blockers (50 M APV, 20 M CNQX, 20 M GABAzine, and 1-2 M CGP55845) and during perfusion of 2 mM external Cs ϩ to block HCN channels.…”
Section: Hcn and Ca V 3 Channels Are Not Required For Autonomous Actimentioning
confidence: 99%
See 1 more Smart Citation
“…Several possibilities have been proposed, including depolarization block due to an increase in potassium current 28 or an inactivation of sodium channels, 29,30 presynaptic depression of excitatory afferents, 31 and stimulation-induced activation of inhibitory afferents. 32,33 Support for the depolarization block hypothesis comes primarily from in vitro experiments. Magariños-Ascone et al, 34 for example, reported that STN cells in rat brain slices increased their instantaneous firing rate during the initial stimulation period, after which these neurons failed to respond.…”
Section: Somatic Activity In the Stimulated Nucleusmentioning
confidence: 99%
“…Hyperpolarization-activated cation (HCN) and low-threshold calcium (T-type) channel currents, for example, may be activated during HFS resulting in an excitatory time-locked rebound. 31,33 The contribution of network and reentrant loops 35 also warrants further investigation with in vivo experiments that incorporate local infusion of specific antagonists during HFS.…”
Section: Somatic Activity In the Stimulated Nucleusmentioning
confidence: 99%